2017
DOI: 10.1186/s12883-017-0903-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Azathioprine metabolites and therapeutic efficacy in Chinese patients with neuromyelitis optica spectrum disorders

Abstract: BackgroundNeuromyelitis optica spectrum disorders (NMOSD) are demyelinating autoimmune diseases in the central nervous system (CNS) that are characterized by a high relapse rate and the presence of anti-aquaporin 4 antibodies (AQP4-IgG) in the serum. Azathioprine (AZA) is a first-line immunomodulatory drug that is widely used for the treatment of patients with NMOSD. However, the efficacy and safety of AZA vary in different individuals.MethodThirty-two patients with NMOSD who regularly took AZA were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Although there were differences in the background of cases in previous studies, most immunosuppressants still significantly decreased the ARR from 1–3 to 0–1 [ 9 , 16 23 ]. Li et al demonstrated that the administration of azathioprine decreased the ARR from 1.41 to 0.36 in 32 cases with NMOSD [ 19 ]. Huang et al demonstrated that mycophenolic acid mofetil for a median duration of 18 months reduced ARR from 1.02 to 0 in 19 cases with NMSOD [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there were differences in the background of cases in previous studies, most immunosuppressants still significantly decreased the ARR from 1–3 to 0–1 [ 9 , 16 23 ]. Li et al demonstrated that the administration of azathioprine decreased the ARR from 1.41 to 0.36 in 32 cases with NMOSD [ 19 ]. Huang et al demonstrated that mycophenolic acid mofetil for a median duration of 18 months reduced ARR from 1.02 to 0 in 19 cases with NMSOD [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various immunosuppressive agents including azathioprine (AZA), mycophenolate mofetil (MMF), and cyclophosphamide (CTX), as well as monoclonal antibodies including rituximab (RTX), eculizumab, and tocilizumab have been reported effective in reducing the annualized relapse rate and stabilizing EDSS scores of NMOSD patients. [38][39][40][41][42] The suggested treatment algorithm for the initiation and maintenance of DMTs is outlined in Figure 2.…”
Section: Initiation and Maintenance Of Dmtsmentioning
confidence: 99%